A Systematic Literature Review of the Potential Therapeutic Effects of Ayahuasca Tea Prepared From the Use of Banisteriopsis Caapi and Psychotria Viridis - Trevisani, Adriane Cordeiro; Trevisani, João Pedro Cordeiro; Haverroth, Moacir; Melo, Ailton da Cruz; Santos, Isabela Carvalho dos; Barbosa, Lidiane Nunes; Gonçalves, Daniela Dib (Journal of Agricultural Studies, 2021)
Ayahuasca is a drink of indigenous origin made as a decoction obtained from medicinal plants found mainly in Acre, state of Brazil, which are the leaves of Psychtoria viridis, popularly known as “chacrona” in Brazil, and the stem of Banisteriopsis caapi, commonly known as mariri or jagube. The decoction is used in religious practices for the therapy of diseases that affect the human being, such as psychological disorders, neurological, parasitic and bacterial infections. Considering the existing bioactive compounds and the therapeutic potential of ayahuasca, this study aims to carry out a literature review of scientific articles (PubMed, Scielo and LILACS) in order to gather knowledge within 30 years of study about the therapeutic potentials of ayahuasca. In the current literature, the studies focus on the area of neuropsychology, dealing with ayahuasca as a form of therapy for neurological and neuromotor disorders. In addition, antimicrobial, antiparasitic, immunomodulatory, and antioxidant actions have already been reported. However, new studies are still needed in these areas in order to evaluate the efficacy and safety of ayahuasca and its component plant species, in order to use it as an alternative therapy, especially in the population from which the traditional knowledge about this beverage came from.